Sleep abnormalities across different clinical stages of Bipolar Disorder: A review of EEG studies. (November 2020) - Zangani, Caroline; Casetta, Cecilia; Saunders, Alejandro Serrano; Donati, Francesco; Maggioni, Eleonora; D'Agostino, Armando
Highlights: Total sleep time and Sleep latency are impaired in all stages of Bipolar Disorder. Increased REM density may precede the onset of the disease. Microarchitecture is a poorly studied, especially sleep spindles. Psychotic versus non-psychotic subjects and within-subject analyses are required. ABSTRACT: Sleep disturbances are highly prevalent across all stages of Bipolar Disorder. Despite a wealth of research on the neurophysiological features of sleep in this population, progress in this field has been slow. We aimed to review the literature on sleep electroencephalography (EEG) studies in Bipolar Disorder, considering sleep architecture and microstructural oscillatory activity. We included a total of 22 studies: six on sleep during manic episodes, seven during depressive episodes, seven in euthymic patients and two in high-risk individuals. The most consistent findings were increased SOL and REM density across all stages of the disorder. Only two studies reported a reduced spindle count during bipolar depression and euthymia, respectively. Although not specific for Bipolar Disorder, SOL and REM density have been repeatedly found to be increased across all stages of illness in this population. Whereas the former reflects a difficulty initiating sleep, the latter can be considered a neurophysiological signature of patients' overall reduced sleep need, independent of illness stage.